Implikasi Pelatihan TikTok Bermuatan Materi Undak – Usuk Bahasa Sunda - Alia, Dwi; Nurzaman, Istikhoroh (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2025)
Along with the times that have entered the industrial era 4.0, introduction or learning should be integrated with the sophistication of digital technology. One of the things that can be used is the social media application tiktok. This service has the aim of directing the use of the TikTok application for more useful educational content, especially with Sundanese language. From the training provided, the results obtained are an increase in children's enjoyment and ability to communicate using Sundanese accompanied by Sundanese language. The feedback from the participants was that this training had a significant positive impact on the use of Sundanese manners in everyday life, because the training was packaged in an interesting way, and the delivery of material was clear and systematic. Efforts to instil character values in children are important as a guide, guideline and reference for children in acting, speaking and behaving in accordance with the values and cultural norms of the Indonesian nation.